Growth, Poverty, Inequality and Well-Being: Regional Contrast in India. Issue 3 (December 2020) - Radhakrishna, R.; Mishra, Brajaraja
This paper analyses the regional dimensions of growth and well-being in the post-reform period. It also analyses the inter-state variations in Gross State Domestic Product (GSDP) per capita. It examines whether disparities in GSDP per capita have narrowed down during the post-reform period. It addresses how economic growth is a determinant of inter-state inequality, performance in poverty reduction and attainment of multidimensional well-being. It identifies factors responsible for widespread inter-state inequality with regard to consumption and multidimensional well-being in general and nutritional attainment in particular. It examines the level and performance of states in reduction of poverty. It also ranks the states on an index of multiple deprivation.